Pendekatan Multidisipliner dalam Studi Perkawinan Dini: A Multidisciplinary Approach in the Study of Early Marriage - Ramzy Faishal Ammar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2026)
Early marriage refers to a marriage that takes place before the prospective bride or groom reaches the minimum age of 19, as stipulated in Law No. 16 of 2019. This study uses a multidisciplinary approach with a thematic-holistic framework to analyze the practice of early marriage in Indonesia. The research method used in this study is library research, which is qualitative in nature, analyzing academic literature, legal regulations, journal articles, and official documents. The multidisciplinary approach provides a comprehensive analytical framework for understanding the factors that cause early marriage and its various impacts, ranging from psychological readiness, social and economic conditions, reproductive health impacts, to gender role construction. The thematic-holistic study emphasizes the importance of the universal values of Islamic family law, such as justice, child protection, emotional and financial readiness, which form the basis for rejecting the practice of early marriage without adequate preparation. The results of the study show that early marriage has a negative impact on mental health, schooling, family stability, and social and economic welfare. A multidisciplinary and thematic-holistic approach provides a more comprehensive analytical framework for formulating appropriate intervention strategies and policies, in line with the principles of maqāṣid al-syarī‘ah and child protection.